A rare case of osteoblastoma combined with severe scoliosis deformity, coronal and sagittal imbalance - Lin-nan Wang; Bo-wen Hu; Lei Wang; Xi Yang; Li-min Liu; Yue-ming Song (BMC Musculoskeletal Disorders, 2017)
Abstract Background Osteoblastoma is a rare and benign tumor which requires early diagnosis and surgical excision. Scoliosis is a common presentation following osteoblastoma. It is considered due to pain-provoked muscle spasm on the side of the lesion. Few researches about osteoblastoma combined with severe scoliosis have been reported. Case presentation A 14-year-old girl presents with progressive scoliosis deformity for 3 years, with gradually appeared low back pain and numbness of left leg. Radiographic results showed osteoblastic mass at the left side of L3-L4 with severe scoliosis deformity, pelvic obliquity and spinal imbalance. The patient underwent posterior tumor excision, spinal decompression, scoliosis correction, spinal fusion with auto-graft and instrumentation from T8-S1. The mass was found to be osteoblastoma. The patient had a full neurological recovery with no aggravate of scoliosis or spinal imbalance during the follow-up. Conclusions This case emphasizes the importance of early diagnosis and surgical treatment of osteoblastoma. Early surgical excision will not only prevent neurological deficit but also the progression of scoliosis. Atypical scoliosis presence without pain requires carefully examination of whether a tumor exists.